Impact of Ownership Structure on Dividend Policies of Indian Non-Financial Firms - Sai Kiran, A.; Ramesh, Kandela (Indian Journal of Finance, 2021)
Our work is based on how ownership structure influenced and impacted dividend payment decisions of Indian non-financial companies that are listed and part of NIFTY 100. Dividend payment is one of the major financial decisions, which has potential to influence the value of companies. As part of ownership structure, which is the main independent variable of the study, we considered shareholding of promoters, foreign institutional investors (FIIs), and domestic institutional investors (DIIs) and investigated the impact of their shareholding on dividend payout decisions, which is the dependent variable in this study. We used return on assets (ROA), debt equity ratio, and size of companies as instrument variables. Our results indicated that ownership structure of Indian non-financial companies is of concentrated type and chiefly concentrated in the hands of promoters and groups. Using two-stage least squares regression model and with the help of instrument variable method, we found promoters, foreign institutional investors, and domestic institutional investors – all to be sharing a significant negative relationship with dividend payment decisions of companies, demonstrating the dominant shareholding type of companies engaged in sharing profits with shareholders in the form of dividends at lower rates and preferring to retain major chunk of profits for future investments and capital requirements.